Analiz ucebno-trenirovocnogo processa regbistov v predsorevnovatel'nom etape - Kokovkin, A. V.; Volodin, V. N.; Yakovlev, D. S.; Gavrilin, I. A. (Vestnik sportivnoj nauki; Sports science bulletin, 2021)
The article deals with the issues of sports training of Rugby players in the Armed Forces of the Russian Federation at the pre-competition stage. The purpose of the article is to analyze and determine the effectiveness of training process. In the course of the study, a variant of microcycles in the study period was proposed. It is revealed that the main volume of training loads is aimed at improving technical and tactical actions of players. The obtained results allow us to assert the effectiveness of the training process of Rugby players in the pre-competition stage.